Pengaruh Kepemimpinan, Lingkungan Kerja Terhadap Semangat Kerja Yang Berdampak Pada Kinerja Pegawai Dinas Sosial Kota Palembang - Dwi Ariestianah; Zunaidah Zunaidah; Omar Hendro (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
This study aims to determine the effect of leadership, work environment on morale which has an impact on the performance of the Palembang City Social Service staff. The research approach is quantitative research with associative research type. The population of this study were 96 employees of the Palembang City Social Service. The sample of this research is calculated by using the Slovin formula, the error rate of 5%, the sample size is 77 employees as respondents. The analysis model used in this research is descriptive statistical analysis, inferential and path analysis. This study aims to answer all problem formulations in the research object. The first conclusion, that leadership has a significant effect on employee morale. Second, the work environment, has a significant effect on employee morale. Third, leadership has a significant effect on the performance of the Palembang City Social Service Employees. Fourth, the work environment has a significant effect on employee performance. Fifth, morale has a significant effect on employee performance. Sixth, leadership through morale has a significant effect on employee performance. Seventh, the environment through morale has a significant effect on the performance of the Palembang City Social Service Employees. A more effective path is the path between leadership and employee performance through employee morale. Researchers provide recommendations, first, it must be maintained that employee morale has the greatest contribution to employee performance and employee work environment. Monitoring and evaluation must be carried out, because leadership towards employee morale is still of low value. Leaders should set a good example so that the performance of the Palembang City Social Service Employees needs to be improved. There needs to be supervision and evaluation from the leadership.